Overview of Children with Covid-19 Confirmation Case in Ulin General Hospital, Banjarmasin, South Kalimantan 15 March - 15 July 2020: Gambaran Kasus Anak dengan Terkonfirmasi Covid-19 di Rumah Sakit Umum Daerah Ulin Banjarmasin Kalimantan Selatan 15 Maret - 15 Juli 2020 - Adelgrit Trisia; Khairiyadi Khairiyadi; Edi Hartoyo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Coronavirus disease (COVID-19) is still a health problem in Indonesia, where the number of cases reported on 10 July 2020 was 72,347, with 3,469 deaths. Banjarmasin City is the 6th highest COVID-19 case after West Java Province. This study aims to describe the case of COVID-19 in pediatric patients treated at Ulin General Hospital, Banjarmasin, South Kalimantan. Method: This study was an observational descriptive study. The data source in this study is the primary data of patients hospitalized from March to July 2020 at Ulin Hospital Banjarmasin. Most COVID-19 occurred in the age group 11-18 years. Most cases of COVID-19 occurred in men (61.11%). 4 patients died. Most comorbidities are kidney failure, malignancy, and hematological disorders. There were 10 patients (55.56%) with clinical and investigative pneumonia examinations. Significant supporting laboratory testing results are an increase in LDH and D-Dimers. Ulin City Hospital, Banjarmasin, South Kalimantan, is a referral hospital with a total number of COVID-19 patients treated by 18 people. Need further research and an increase in inpatient cases at Ulin City Hospital Banjarmasin.